Identification of Angiotensin I-converting enzyme Inhibitory Activities from traditional Mongolian fermented milk products - Bayarsaikhan, D; Yamaki, Kohji; Enkhtaivan, G; Ichinkhorloo, Z (Mongolian Journal of Chemistry, 2014)
Several angiotensen-converting enzyme (ACE) inhibitory peptites have been detected in milk products. There are many traditional milk products in Mongolia. For this study, some Mongolian milk products were collected, and the ACE inhibitory activities of these samples were tested; an active fraction was found in aaruul made from mare’s milk. After purification by dialysis and HPLC, the active fractions were isolated. The molecular weight of the active component was 362.05 M, as determined by mass spectrometry. An authentic standard was used to determine the IC50 value of the inhibitory activity. From 5’-GMP is not much higher than that of the active peptide in sour milk and some flavonoids. However, this is the first report that shows that 5’ –GMP inhibits ACE activity. These results will provide useful information for the development of hypertension therapy agents. DOI: http://dx.doi.org/10.5564/mjc.v12i0.175 Mongolian Journal of Chemistry Vol.12 2011: 65-68